FAMILY AND COMPANIONSHIP: THE ESTABLISHMENT OF PROTECTIVE AND WELFARE SOCIAL RELATIONS IN BELÉM IN THE BELLE ÉPOQUE - Corrêa, Ana Maria Maciel (Seven Editora, 2025)
This text is based on the socio-historical approach regarding the value of family life established by marital relations and godparenthood, understood as spiritual kinship. As references sedimented by the relations between individuals and groups in the society of Pará in the Belle Époque. Historical context constructing and affirming social networks between groups located horizontally and/or vertically. Social places of reaffirmation of power and dominance, as well as of dependence and subordination. Social relations are mediated by the practices or obligations of “giving, receiving, and reciprocating” the gifts received. A relational system is very present in the Brazilian coronel system. In this context, family life as an interactive social space reveals the social plots and networks in the social, political, and economic spheres, which guide obligations between peers and other social groups through protective and welfare actions present in family and godparenthood relations. The text is based on analyses by Brazilian historians, sociologists, and researchers from Pará who substantiate the problematization and understanding of Brazilian and Pará society. DOI: https://doi.org/10.56238/sevened2024.037-178